Experimental determination of Ni isotope fractionation during Ni adsorption from an aqueous fluid onto calcite surfaces. (15th March 2020) - Castillo Alvarez, Cristina; Quitté, Ghylaine; Schott, Jacques; Oelkers, Eric H.
Abstract: The fractionation of Ni isotopes during Ni adsorption from aqueous fluids onto calcite surfaces was measured at 25 °C and as a function of pH from 7.7 to 8.9. Experiments showed that the percent Ni adsorbed and the degree of Ni isotope fractionation attained constant values in less than 30 hours after the calcite was exposed to the Ni bearing, calcite saturated aqueous solution. The percentage of Ni adsorbed from the fluid onto the calcite surfaces increased from 9 to 67% as the pH increased over this range. Calcite preferentially adsorbs light Ni isotopes during adsorption, resulting in a fractionation between adsorbed and aqueous, Δ 60 Nicalcite-fluid, of −0.52 ± 0.16‰. This value is pH independent, within uncertainty, over the experimental pH range. The preferential adsorption of light Ni isotopes into calcite likely results from the change in coordination environment between adsorbed and aqueous nickel; the NiO length in the NiCO3 bond formed at the calcite surface is greater than that in the Ni 2+ aquo ion.